β-Cell–Specific Protein Kinase A Activation Enhances the Efficiency of Glucose Control by Increasing Acute-Phase Insulin Secretion - Kaihara, Kelly A. (American Diabetes Association, 2013)
Acute insulin secretion determines the efficiency of glucose clearance. Moreover, impaired acute insulin release is characteristic of reduced glucose control in the prediabetic state. Incretin hormones, which increase β-cell cAMP, restore acute-phase insulin secretion and improve glucose control. To determine the physiological role of the cAMP-dependent protein kinase (PKA), a mouse model was developed to increase PKA activity specifically in the pancreatic β-cells. In response to sustained hyperglycemia, PKA activity potentiated both acute and sustained insulin release. In contrast, a glucose bolus enhanced acute-phase insulin secretion alone. Acute-phase insulin secretion was increased 3.5-fold, reducing circulating glucose to 58% of levels in controls. Exendin-4 increased acute-phase insulin release to a similar degree as PKA activation. However, incretins did not augment the effects of PKA on acute-phase insulin secretion, consistent with incretins acting primarily via PKA to potentiate acute-phase insulin secretion. Intracellular calcium signaling was unaffected by PKA activation, suggesting that the effects of PKA on acute-phase insulin secretion are mediated by the phosphorylation of proteins involved in β-cell exocytosis. Thus, β-cell PKA activity transduces the cAMP signal to dramatically increase acute-phase insulin secretion, thereby enhancing the efficiency of insulin to control circulating glucose.